Ekonomi Politik Media Dalam YouTube Sebagai Ruang Publik Komunikasi Pariwisata Jawa Barat - Gayatri Atmadi; Udi Rusadhi Rusadhi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
The emergence of social media youtube with its practical, informative and efficient nature makes many people love it today. YouTube social media has many benefits, such as to search for movies, listen to music, watch the latest videos, and others. This study aims to explore the use of youtube according to the perspective of media political economy and Jurgen Habermas's thoughts on public sphere. Through a tourism communication approach, this research is included in the type of qualitative research with a discourse analysis research method based on storytelling video impressions produced by Kompas Daily entitled "Hidden Paradise in the South of West Java" as a recommendation for tourist attractions in West Java besides Bandung and Puncak. The results showed that the study of the political economy of media on YouTube platform explained that YouTube media companies are run to satisfy the needs and desires to obtain a variety of information for audiences and advertisers with available resources. The existence of social relations in the field of communication in YouTube media can obscure economic relations that reflect the pattern of greater digital capitalist development. Through the understanding of YouTube media as a public sphere, the conclusion of the study shows that YouTube users have consciously or unconsciously become "employees" for the YouTube media industry by becoming prosumers who are able to produce media content by sending video posts, showing likes or dislikes, commenting and making links when they become consumers on their social media.